The Distance of Marketing Knowledge and Its Role in Achieving Customer Satisfaction: An Analytical Study of The Opinions of a Sample of Members of The Civil Banks in Erbil - Himdad Zaher Nory; Dlawar Jalal Ghareeb (QALAAI ZANIST JOURNAL, 2023)
The study aims to identify and find the relationship and impact in the application of marketing knowledge to customer satisfaction as well as in its modern concept, and the application of marketing knowledge expresses the independent variable represented by its dimensions the broad marketing mix (7ps), (service, price, distribution, promotion, individuals, physical evidence, operations) on the dependent variable customer satisfaction. To answer the problem of the study, four main hypotheses were presented to test them and the research was divided into two parts, the first then by addressing the theoretical aspects related to the two study variables, while the second represents the field aspect of the study, through which a real study was carried out the existence of the influential relationship between the two variables of the study in the expenses researched formed (6) private banks, where the questionnaire form was randomly distributed (190) forms were retrieved (170) forms of which (152) forms were valid for analysis. After emptying the data obtained from the responses of the sample members to the questionnaire questions in the statistical analysis program (spss) and running the program, a set of results were reached. The existence of a strong correlation between the two variables and their dimensions at the macro and micro level if the correlation coefficients are high and these results confirm the strong correlation between the two variables. The results confirmed the existence of a moral impact of marketing knowledge and customer satisfaction at the general level and this indicates the interest of the management of the researched banks in the practice of the dimensions of marketing knowledge, represented by the broad marketing mix in order to achieve customer satisfaction. Based on the results, the researcher presented a set of proposals, the most important of which are: The study recommends the need to adopt the demands and desires of the relevant customers that go beyond the nature of the current banking services of banks by relying on the results of market research to diagnose the new needs of the relevant parties. The study concluded with a set of future study proposals to help researchers to research them in studies and research relevant to the current study variables.